Effects of Gut Microbiome and Short-Chain Fatty Acids (SCFAs) on Finishing Weight of Meat Rabbits - Fang, Shaoming; Chen, Xuan; Ye, Xiaoxing; Zhou, Liwen; Xue, Shuaishuai; Gan, Qianfu (Frontiers in Microbiology, 2020)
Understanding how the gut microbiome and short chain fatty acids (SCFAs) affect finishing weight is beneficial to improve meat production in the meat rabbit industry. In this study, we identified 15 OTUs and 23 microbial species associated with finishing weight using 16S rRNA gene and metagenomic sequencing analysis, respectively. Among these, butyrate-producing bacteria of the family Ruminococcaceae were positively associated with finishing weight, whereas the microbial taxa related to intestinal damage and inflammation showed opposite effects. Furthermore, interactions of these microbial taxa were firstly found to be associated with finishing weight. Gut microbial functional capacities analysis revealed that CAZymes, such as galactosidase, xylanase, and glucosidase, could significantly affect finishing weight, given their roles in regulating nutrient digestibility. GOs related to the metabolism of several carbohydrates and amino acids also showed important effects on finishing weight. Additionally, both KOs and KEGG pathways related to the membrane transportation system, and involved in aminoacyl-tRNA biosynthesis and butanoate metabolism could act as key factors in modulating finishing weight. Importantly, gut microbiome explained nearly 11% of the variation in finishing weight, and our findings revealed that a subset of metagenomic species could act as predictors of finishing weight. SCFAs levels, especially butyrate level, had critical impacts on finishing weight, and several finishing weight associated species were potentially contributed to the shift in butyrate level. Thus, our results should give deep insights into how gut microbiome and SCFAs influence finishing weight of meat rabbits and provide essential knowledge for improving finishing weight by manipulating gut microbiome.